Tele-ophthalmological check-up in nursing homes: results from the TOVIS pilot study : research letter - Emde, Leon von der; Gruber, Claus; Arend, Lilith; Finger, Robert P.; Nadal, Jennifer; Schmid, Matthias; Holz, Frank G.; Ach, Thomas (Deutsches Ärzteblatt, 2025)
In Germany, approximately 800 000 elderly people (1) live in around 13 600 nursing homes; this population faces significant shortcomings in terms of ophthalmic care, already today and in the future (2). The OVIS and SÄVIP studies showed that a large...
Gesehen am 26.08.2025